Polska Szkoła Biblioterapii - Chatzipentidis, Kiriakos; Czernianin, Wiktor (2016)
1. The state of contemporary research in bibliotherapy 2. Educational and methodological textbooks in field of bibliotherapy; 3. Development trends in field of bibliotherapy.
Keywords: bibliotherapy textbooks; bibliotherapy in Poland; teaching of bibliotherapy; development trends of bibliotherapy